Principles of Food Sanitation - Marriott, Norman G.; Schilling, M. Wes; Gravani, Robert B. (Food Science Text Series, 2018)
Now in its 6th Edition, this highly acclaimed textbook provides sanitation information needed to ensure hygienic practices and safe food for food industry personnel as well as students. It addresses the principles related to contamination, cleaning compounds, sanitizers, cleaning equipment. It also presents specific directions for applying these concepts to attain hygienic conditions in food processing or food preparation operations. New in this edition: Updated chapters on the fundamentals of food sanitation, contamination sources and hygiene, Hazard Analysis Critical Control Points, cleaning and sanitizing equipment, waste handling disposal, biosecurity, allergens, quality assurance, pest control, cleaning compound and sanitizer properties and selection criteria, hygienic construction, sanitation guidelines for food and foodservice establishments, and sanitation management principles.